Polishing agent for low-alloy weld metal EBSD sample, method and application
By using a polishing agent composed of citric acid and silica suspension for vibration polishing, the problem that low alloy steel weld metal is difficult to meet the detection and analysis requirements due to point corrosion problems in EBSD detection and analysis was solved, and the high hit rate of EBSD samples was achieved, which improved the welding quality and the level of new technology research.
Patent Information
- Application Number
- CN202411751592.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-04
AI Technical Summary
In EBSD detection and analysis, due to pit corrosion problems, it is difficult to meet the requirements of detection and analysis, resulting in limited welding quality and new technology research.
Vibration polishing is performed using a polishing agent composed of citric acid and silica suspension to remove the surface deformation layer without causing pitting corrosion, and the hit rate of the EBSD sample is improved.
Through this method, the hit rate of the low alloy weld metal EBSD sample reaches more than 98%, solving the problem of point corrosion, meeting the requirements of EBSD detection and analysis, and improving the level of welding quality and new technology research.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metallographic detection, in particular to a polishing agent, a method and an application thereof for EBSD samples of low alloy weld metals. Background Art
[0002] Welding is a key process in nuclear power equipment manufacturing and a core technology for considering manufacturing level. Welding quality is an important guarantee for the safe operation of nuclear power. EBSD technology is widely used in the research of welding quality and new technologies, and in the detection and analysis of cladding metal, fusion line and heat affected zone. However, EBSD detection and analysis requires that the surface of the sample has no stress layer, no oxide layer, no continuous corrosion pits, the surface undulation cannot be too large, and the surface is clean and pollution-free. Figure 1 . Low alloy steel is widely used in nuclear power equipment. Due to the relatively low content of alloying elements in low alloy steel, the acid and alkali corrosion resistance of low alloy steel weld metal is lower. Welding is a process of weld metal smelting, involving the transformation of weld metal and heat-affected zone. Compared with the parent material, the weld metallographic structure is more complex and special. For example, its spatial state is mainly axial and dendritic. Therefore, there is natural microsegregation in the weld metal, low melting point impurity elements gather between dendrites, and the weld metal inevitably has slag inclusions and other characteristics. These characteristics further reduce the corrosion resistance of low alloy steel weld metal.
[0003] Sample preparation is a key process in EBSD detection and analysis research. Conventional EBSD vibration polishing sample preparation is: through reasonable wire cutting-mounting-metallographic grinding and polishing, the sample detection surface is made to a mirror-like scratch-free state, and then the sample detection surface deformation layer is removed by oxygen-free vibration polishing before EBSD detection and analysis can be performed. The use of polishing agents in the industry will cause pitting corrosion of low-alloy steel weld metal. Usually, low-alloy steel weld metal EBSD samples must be vibrated and polished in a suspension for a sufficient time during vibration polishing to remove the deformation layer. When the sample vibration polishing is completed, the sample detection surface has been severely pitted and cannot meet the EBSD detection and analysis requirements. See Figure 2 .
[0004] In order to use EBSD to detect and develop low alloy steel weld technology for nuclear power equipment, it is necessary to develop a preparation method and construction process suitable for low alloy steel weld samples that does not produce pitting corrosion during EBSD oxygen-free vibration polishing. Summary of the invention
[0005] In view of the above problems, the present invention provides a polishing agent for preparing EBSD samples of low-alloy weld metal. Vibration polishing based on the polishing agent can make the hit rate of the prepared low-alloy weld metal EBSD sample reach more than 98%.
[0006] In order to achieve the above object, the present invention provides a polishing agent for preparing low alloy weld metal EBSD samples, which is mainly composed of citric acid and silicon dioxide suspension.
[0007] Vibration polishing based on the above polishing agent can prevent pitting corrosion of low alloy steel weld samples and remove the surface deformation layer, so that the hit rate of the prepared low alloy weld metal EBSD sample can reach more than 98%. The citric acid used is commonly used as a food additive, which is easy to obtain, economical, practical and environmentally friendly.
[0008] In one embodiment, the pH value of the polishing agent is 5-6.
[0009] The present invention also provides a method for preparing the polishing agent, comprising the following steps: preparing a citric acid solution, adding the citric acid solution into a silicon dioxide suspension until the pH value is 5-6, and obtaining the polishing agent.
[0010] The present invention also provides a method for preparing a low-alloy weld metal EBSD sample, comprising the following steps: using water and the polishing agent as a polishing solution, performing a first vibration polishing on the sample to be polished, washing, using water as a polishing solution to perform a second vibration polishing, washing, ultrasonic cleaning, and drying to obtain a low-alloy weld metal EBSD sample.
[0011] This method is suitable for the EBSD sample preparation of low alloy steel and low alloy steel weld metal. The sample has the surface deformation layer removed in a weighted environment without being pitted; ultrapure water vibration polishing not only further removes the deformation layer and cleans the polished surface, but also the final EBSD hit rate of the sample can reach more than 98%. This method is solidifiable, simple to operate, green and environmentally friendly, economical and practical. Different operators can prepare qualified EBSD samples of low alloy steel weld metal according to this scheme.
[0012] In one embodiment, the sample to be polished is a low alloy weld metal, the first vibration polishing time is 20-30 minutes, and the second vibration polishing time is 25-35 minutes.
[0013] In one embodiment, the sample to be polished is loaded with a weight, and the weight is 550-650g.
[0014] In one embodiment, the sample to be polished is obtained by sample cutting, cold mounting, grinding and polishing.
[0015] The present invention also provides an electron backscatter diffraction detection method for low alloy weld metal, comprising the following steps: performing electron backscatter diffraction detection on the EBSD sample for preparing low alloy weld metal prepared by the method.
[0016] The present invention also provides application of the electron backscatter diffraction detection method in the preparation of nuclear power equipment.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The polishing agent, method and application for EBSD samples of low alloy weld metal of the present invention, based on the polishing agent, vibration polishing is performed, the low alloy steel weld sample will not be pitted, and the surface deformation layer is removed, so that the hit rate of the prepared low alloy weld metal EBSD sample can reach more than 98%. The problem that the sample cannot meet the EBSD detection and analysis requirements due to pitting corrosion during vibration polishing of low alloy steel welds is solved, and EBSD detection and analysis of low alloy steel welds can be performed, so as to improve welding quality and research on new technologies. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 To meet the basic morphology of samples for EBSD detection and analysis; Figure 2 This is the pitting corrosion morphology of a low alloy steel weld sample after conventional vibration polishing; Figure 3 BC+IPF+GB surface distribution of EBSD of SA-508Gr3.Cl1 weld in Example 1 (hit rate 98.8%); Figure 4 BC+IPF+GB surface distribution of EBSD of 16MND5 weld in Example 2 (hit rate 98.6%); Figure 5 BC+IPF+GB surface distribution of EBSD of SA-508Gr3.Cl1 weld in comparative example 1 (hit rate 34.5%); Figure 6 This is the BC+IPF+GB surface distribution of the EBSD of the SA-508Gr3.Cl1 weld in Comparative Example 2 (hit rate 51.7%). DETAILED DESCRIPTION
[0019] In order to facilitate the understanding of the present invention, the present invention will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present invention are given in the drawings. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0021] source: Unless otherwise specified, the reagents, materials, and equipment used in this example are all commercially available; the experimental methods are all conventional experimental methods in the art unless otherwise specified.
[0022] definition: Low alloy: in the present invention, it means that the total amount of alloy elements is less than 5%.
[0023] Weld metal: refers to the metal formed after the molten electrode or wire fuses with the base metal during the welding process.
[0024] Example 1 Weld sample made of SA-508Gr3.Cl1. 1. Preliminary sample preparation
[0025] The weld samples made of SA-508Gr3.Cl1 are cut into samples with a length of 8~20mm, a width of 8~20mm, and a thickness of 2~3mm according to the requirements of the detection position, and are cold mounted into Φ40×20mm blocks (the size can be determined according to the grinding tool used). The mounted samples are ground with 300 mesh, 600 mesh, 800 mesh, and 1200 mesh water sandpaper in sequence to a smooth and delicate surface, and then polished. The polishing is carried out with 7μm, 3.5μm, 1.5μm, and 0.5μm diamond spray in sequence to a smooth and clean mirror surface.
[0026] 2. Prepare citric acid suspension.
[0027] Step 1: Pour 0.05 g of analytical grade citric acid into 40 ml of distilled water.
[0028] Step 2: Pour 20ml of the prepared citric acid aqueous solution in step 1 into 20ml of SiO2 suspension, stir evenly and measure the pH value with a pH test paper, which should be 5~6.
[0029] Step 3: Add 200 ml of distilled water to the vibration plate and evenly pour the citric acid suspension prepared in step 2.
[0030] 3. Vibration polishing.
[0031] The prepared samples were placed in a vibration polishing mold and loaded with a 600g weight. The samples were vibrated and polished for 25 minutes. The samples were taken out and rinsed with running water for 2 minutes. At the same time, the citric acid SiO2 suspension in the polishing disk was poured out and rinsed clean. Then 250ml of distilled water was added again and vibration polished for another 30 minutes. After the vibration polishing was completed, the samples were taken out and rinsed with running water for 2 minutes. After being placed in a beaker and added with anhydrous ethanol, they were ultrasonically cleaned for 10 minutes. After being blown dry, the samples were taken out of the mosaic mold and placed in the SEM for EBSD detection and analysis. The hit rate reached 98.8%, the distribution diagrams were clear, and the collected data were complete. The results are shown in Figure 3 .
[0032] Example 2 Weld sample made of 16MND5 material.
[0033] 1. Preliminary sample preparation
[0034] The weld samples made of 16MND5 are cut into samples with a length of 8~20mm, a width of 8~20mm, and a thickness of 2~3mm according to the requirements of the detection position, and are cold mounted into Φ40×20mm blocks (the size can be determined according to the abrasive tool used). The mounted samples are ground with 300 mesh, 600 mesh, 800 mesh, and 1200 mesh water sandpaper in sequence to a smooth and delicate surface, and then polished. The polishing is carried out with 7μm, 3.5μm, 1.5μm, and 0.5μm diamond spray in sequence to a smooth and clean mirror surface.
[0035] 2. Prepare citric acid suspension.
[0036] Step 1: Pour 0.05 g of analytical grade citric acid into 40 ml of distilled water.
[0037] Step 2: Pour 20ml of the prepared citric acid aqueous solution in step 1 into 20ml of SiO2 suspension, stir evenly and measure the pH value with a pH test paper, which should be 5~6.
[0038] Step 3: Add 200 ml of distilled water to the vibration plate and evenly pour the citric acid suspension prepared in step 2.
[0039] 3. Vibration polishing.
[0040] The prepared samples were placed in a vibration polishing mold and loaded with a 600g weight. The samples were vibrated and polished for 25 minutes. The samples were taken out and rinsed with running water for 2 minutes. At the same time, the citric acid SiO2 suspension in the polishing disk was poured out and rinsed clean. Then 250ml of distilled water was added again and vibration polished for another 30 minutes. After the vibration polishing was completed, the samples were taken out and rinsed with running water for 2 minutes. After being placed in a beaker and added with anhydrous ethanol, they were ultrasonically cleaned for 10 minutes. After being blown dry, the samples were taken out of the mosaic mold and placed in the SEM for EBSD detection and analysis. The hit rate reached 98.6%. The distribution diagrams were clear and the collected data were complete. The results are shown in Figure 4 .
[0041] Comparative Example 1 Weld sample made of SA-508Gr3.Cl1.
[0042] 1. Preliminary sample preparation
[0043] The weld samples made of SA-508Gr3.Cl1 are cut into samples with a length of 8~20mm, a width of 8~20mm, and a thickness of 2~3mm according to the requirements of the detection position, and are cold mounted into Φ40×20mm blocks (the size can be determined according to the grinding tool used). The mounted samples are ground with 300 mesh, 600 mesh, 800 mesh, and 1200 mesh water sandpaper in sequence to a smooth and delicate surface, and then polished. The polishing is carried out with 7μm, 3.5μm, 1.5μm, and 0.5μm diamond spray in sequence to a smooth and clean mirror surface.
[0044] 2. Prepare the suspension.
[0045] Add 200 ml of distilled water to the vibrating plate and pour 20 ml of SiO2 suspension evenly into it.
[0046] 3. Vibration polishing.
[0047] The prepared samples were placed in a vibration polishing mold and loaded with a 600g weight. The samples were vibrated and polished for 25 minutes. The samples were taken out and rinsed with running water for 2 minutes. The SiO2 suspension in the polishing disk was poured out and rinsed clean. Then 250ml of distilled water was added again and vibration polished for another 30 minutes. After the vibration polishing was completed, the samples were taken out and rinsed with running water for 2 minutes. After being placed in a beaker and adding anhydrous ethanol, they were ultrasonically cleaned for 10 minutes. After being blown dry, the samples were taken out of the mosaic mold and placed in SEM for EBSD detection and analysis. The hit rate was only 34.5%, the pitting corrosion interference was serious, the distribution diagrams were unclear, the microstructure could not be distinguished, and the collected data had no analytical value. The results are shown in Figure 5 .
[0048] Comparative Example 2 Weld sample made of SA-508Gr3.Cl1.
[0049] 1. Preliminary sample preparation
[0050] The weld samples made of SA-508Gr3.Cl1 are cut into samples with a length of 8~20mm, a width of 8~20mm, and a thickness of 2~3mm according to the requirements of the detection position, and are cold mounted into Φ40×20mm blocks (the size can be determined according to the grinding tool used). The mounted samples are ground with 300 mesh, 600 mesh, 800 mesh, and 1200 mesh water sandpaper in sequence to a smooth and delicate surface, and then polished. The polishing is carried out with 7μm, 3.5μm, 1.5μm, and 0.5μm diamond spray in sequence to a smooth and clean mirror surface.
[0051] 2. Prepare glacial acetic acid suspension.
[0052] Step 1: Pour 1 ml of glacial acetic acid into 40 ml of distilled water.
[0053] Step 2: Pour 3 ml of the glacial acetic acid aqueous solution prepared in step 1 into 20 ml of SiO2 suspension, stir evenly and measure with pH paper. The value should be 5~6.
[0054] Step 3: Add 230 ml of distilled water to the vibration plate and evenly pour the glacial acetic acid suspension prepared in step 2.
[0055] 3. Vibration polishing.
[0056] The prepared samples were placed in a vibration polishing mold and loaded with a 600g weight. The samples were vibrated and polished for 25 minutes. The samples were taken out and rinsed with running water for 2 minutes. At the same time, the glacial acetic acid SiO2 suspension in the polishing disk was poured out and rinsed clean. Then 250ml of distilled water was added again and vibration polished for another 30 minutes. After the vibration polishing was completed, the samples were taken out and rinsed with running water for 2 minutes. After being placed in a beaker and added with anhydrous ethanol, they were ultrasonically cleaned for 10 minutes. After being blown dry, the samples were taken out of the mosaic mold and placed in SEM for EBSD detection and analysis. The hit rate was only 51.7%, the distribution diagrams were not clear, the microstructure could not be distinguished, and the collected data had no analytical value. The results are shown in Figure 6 .
[0057] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0058] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A polishing agent for preparing EBSD samples of low alloy weld metals, characterized in that: It is mainly composed of citric acid and silicon dioxide suspension.
2. The polishing agent according to claim 1, characterized in that The pH value of the polishing agent is 5-6.
3. The method for preparing the polishing agent according to any one of claims 1 to 2, characterized in that: The following steps are involved: A citric acid solution is prepared, and the citric acid solution is added to the silicon dioxide suspension to a pH value of 5-6 to obtain a polishing agent.
4. A method for preparing EBSD samples of low alloy weld metals, characterized in that: The following steps are involved: Using water and the polishing agent described in any one of claims 1-2 as the polishing solution, the sample to be polished is subjected to a first vibration polishing, washed, and then subjected to a second vibration polishing, washed, ultrasonically cleaned, and dried to obtain a low-alloy weld metal EBSD sample.
5. The method according to claim 4, characterized in that The sample to be polished is a low alloy weld metal, the first vibration polishing time is 20-30 minutes, and the second vibration polishing time is 25-35 minutes.
6. The method according to claim 4, characterized in that The sample to be polished is loaded with a weight, and the weight is 550-650g.
7. The method according to any one of claims 4 to 6, characterized in that: The sample to be polished is obtained by sample cutting, cold mounting, grinding and polishing.
8. An electron backscatter diffraction detection method for low alloy weld metal, characterized in that: The method comprises the following steps: performing electron backscatter diffraction detection on an EBSD sample for preparing low alloy weld metal obtained by the method described in any one of claims 4 to 7.
9. Application of the electron backscatter diffraction detection method according to claim 8 in the preparation of nuclear power equipment.
Citation Information
Cited By
Polishing agent for low-alloy weld metal EBSD sample, method, and use
WO2026118681A1